Stress Analysis on The Bellows Component in 150KV SF6 Gas Insulated Switchgear - William Sebastian Napitupulu - 13114104, Theo
Electricity is a primary need of human life in the globalization era, including Indonesia. Need of electricity in Indonesia continue to increase every year in accordance with the goverment’s target of 97% in 2019. Along with the increasing of electricity demand in Indonesia, it must be accompanied by an increase of generators usage and electricity distribution infrastructure in Indonesia. Gas Insulated Switchgear (GIS) is a connecting system and electrical network breaker which is packaged using SF6 gas as an electrical insulation material and arc burners that may occur between conductors. One of the most critical component of GIS system is bellows. The main function of bellow is to overcome position difference of the components of GIS and prevent SF6 gas leakage to the enviroment which has a lot of adverse effects, also endanger the surrounding GIS systems area and increase the risk of short circuit between conductors in the GIS system. In one of the GIS systems in Indonesia, the bellow component leaked so that the SF6 gas spread out into the enviroment so that stress analysis is needed using Finite Element Analysis (FEA) to determine the possible causes of bellow’s leakage. FEA results using ANSYS 15.0 and Autodesk Inventor Professional 2018 show that lateral direction of movement or deflection in one end of the bellow is the most likely parameter to cause bellow’s failure which is about 4 cm of lateral deflection.